Multimodal analysis for critical thinking - O'Halloran, Kay; Tan, Sabine; E, M. (2015)
This paper proposes a pedagogical approach for teaching and learning critical thinking through multimodal analysis – that is, ‘multimodal analysis for critical thinking'. The approach builds on the conviction that students require competencies that move beyond traditional notions of literacy to meet the changing demands posed by media and technology in the twenty-first century. The approach takes a social semiotic view toward critical multimodal literacy, which aims to provide students with an analytical metalanguage for the systematic analysis of multimodal texts and videos. The pedagogical approach is facilitated through the use of purpose-built software applications with comprehensive analytical frameworks designed to support the systematic teaching and learning of multimodal analysis, with a view to developing the critical literacy skills needed for life in the digital age. The potential efficacies of the approach are illustrated via the exposition of software functionalities and the sample analyses of a printed text with image components, and a short advocacy video.